2019
DOI: 10.1186/s13569-019-0113-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide methylation profiling and copy number analysis in atypical fibroxanthomas and pleomorphic dermal sarcomas indicate a similar molecular phenotype

Abstract: Background Atypical fibroxanthomas (AFX) and pleomorphic dermal sarcomas (PDS) are lesions of the skin with overlapping histologic features and unspecific molecular traits. PDS behaves aggressive compared to AFX. Thus, a precise delineation, although challenging in some instances, is relevant. Methods We examined the value of DNA-methylation profiling and copy number analysis for separating these tumors. DNA-methylation data were generated from 17 AFX and 15 PDS using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 37 publications
1
43
1
8
Order By: Relevance
“…The DNAmethylation profiles of AFX/PDS argue for a common tumor spectrum. 1 Atypical fibroxanthoma often presents as a red nodule or plaque, with or without ulceration. The head-and-neck region is preferred although tumors may occur on other body parts as well.…”
Section: Introductionmentioning
confidence: 99%
“…The DNAmethylation profiles of AFX/PDS argue for a common tumor spectrum. 1 Atypical fibroxanthoma often presents as a red nodule or plaque, with or without ulceration. The head-and-neck region is preferred although tumors may occur on other body parts as well.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular studies have failed to demonstrate alterations substantially discriminating AFX from PDS, to date [6][7][8] , inducing some authors to consider AFX as the "not infiltrating precursor of PDS" 8 . From the immunohistochemical point of view, we did not find a different profile among tumors with different cellular types.…”
Section: Discussionmentioning
confidence: 99%
“…Pleomorphic dermal sarcoma (PDS) is a tumor with overlapping clinical, pathological and immunophenotypical features, but with higher recurrence rate and metastatic potential 4,5 . Recent studies found similar genetic alterations in the two neoplasms 6‐8 . Both AFX and PDS are diagnoses of exclusion, to be made after careful immunohistochemical study, in order to not miss other neoplasms such as squamous cell carcinoma, melanoma, leiomyosarcoma or angiosarcoma 9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative genomic hybridisation demonstrated similar mutation profiles in genes like FAT1 , NOTCH1 and 2 , CDKN2A , TP53 and TERT promoter, but activating RAS and PIK3CA mutations only in a small number of DPS [7], [8].…”
Section: Discussionmentioning
confidence: 99%